2004
DOI: 10.1515/jpm.2004.125
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged fetal bradycardia as the presenting clinical sign in Streptococcus agalactiae chorioamnionitis

Abstract: Group B Streptococcus remains a leading infectious cause of neonatal morbidity and mortality. We report a case of a 37 weeks' gestation infant with severe birth asphyxia, status epilepticus and GBS chorioamnionitis, in which a prolonged fetal bradycardia was the only prenatal clinical sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Abnormal heart-rate characteristics of reduced variability and transient decelerations precede the clinical signs of sepsis and sepsis-like illness in neonates (15)(16)(17)(18). We have recently observed that persistent fetal heart rate hypovariability as well as prolonged fetal bradycardia may be unrecognized signs of HCA (12,13). Antepartum fetal monitoring with classic cardiotocography has been used for checking fetal status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal heart-rate characteristics of reduced variability and transient decelerations precede the clinical signs of sepsis and sepsis-like illness in neonates (15)(16)(17)(18). We have recently observed that persistent fetal heart rate hypovariability as well as prolonged fetal bradycardia may be unrecognized signs of HCA (12,13). Antepartum fetal monitoring with classic cardiotocography has been used for checking fetal status.…”
Section: Discussionmentioning
confidence: 99%
“…Although no early, noninvasive, validated, accurate markers of HCA in preterm newborns are available, recent research indicates that abnormal heart rate variability is associated with HCA in the term fetus (12,13). Administration of endotoxin to an experimental newborn model has been shown to lead to an altered balance of autonomic tone, with reduced beat-to-beat heart rate variability (14).…”
mentioning
confidence: 99%
“…C horioamnionitis is a typical disease of the second trimester of gestation and is associated with preterm birth with increased fetal and neonatal morbidity and mortality, as well as a higher risk of damage to the white matter of the brain and cerebral palsy. 1 2 Little information on the effects of chorioamnionitis in the term fetus/newborn is available, although reported complications include depressed Apgar scores, neonatal encephalopathy with increased risk of developing cerebral palsy, [2][3][4][5][6] infection, high risk of intubation in the delivery room, 7 fetal death, 8 and fetal growth restriction. 9 A large proportion of cases of chorioamnionitis remain subclinical (histological chorioamnionitis (HCA)), 1 10 11 without sufficiently accurate clinical signs at birth being known to date.…”
mentioning
confidence: 99%
“…Hypertension and diabetes are among maternal comorbid causes of chronic fetal distress. [31][32][33][34][35] Miscellaneous maternal causes include hypothermia; poisoning from organophosphates, carbamates, and methanol; seizures; and metabolic abnormalities such as hypoglycaemia. [22][23][24][25][26][27] Recreational drugs, chiefly cocaine, can induce fetal bradycardia.…”
Section: Fetal-maternal Conditionsmentioning
confidence: 99%